(untitled) (Politeja, 2024)
BURY OR GIVE A NEW LIFE? THE BENEFITS OF THE COALITION OF THE WEIMAR TRIANGLE COUNTRIES IN THE LEGISLATIVE PROCESS OF THE EUROPEAN UNION The article seeks to answer the following question: does building a Weimar coalition, understood as agreeing on a common policy position on EU legislation, increase the bargaining success of the Weimar Triangle (WT) countries when adopting EU secondary law? For this purpose, a statistical analysis was carried out to empirically test the hypothesis that Germany, France and Poland are more successful in realizing their preferences when they form a coalition. The following results were obtained. First, the possibilities of building a Weimar coalition in the EU legislative process are limited. In the years 2004-2019, WT countries held a common position on only 25% of EU legislative files, while the country that most often broke the Weimar coalition, was Poland. Second, despite its low frequency, building a Weimar coalition is generally very profitable. When WT countries form an alliance, the average bargaining success of these countries taken together increases compared to the absence of such a coalition. Third, building a Weimar coalition is not equally beneficial for all WT members treated individually. While it increases the bargaining success of Poland and France, this relationship does not exist in the case of Germany.